Risks in construction supply chain - Ahmad, Zaid (2019)
Pakistan's construction industry is constantly evolving and is associated with high and critical risk factors that is close relating to the success and failure of a construction project. One of the most critical factors that affect the construction project is disrupted the supply chain in construction. Disruption in construction supply chain occurs due to many risk factors that occur during the project life cycle. The research is aimed to identify the critical risk factors that occur in a construction supply chain, by analyzing the occurrence of risk factors through quantitative and qualitative research methods. Furthermore the identified risks require to be prioritized and classified through the project stages. Therefor, contemporary and traditional methods of supply chain risk management were review to understand the various existing practices. Various challenges and opportunities were explored, and awareness of supply chain risk management in Pakistan construction industry was studied. The outcome of the research is to propose an integrated framework for managing supply chain risks in the construction project life cycle. The resulting framework will comprise of a structured classification for prioritizing supply chain risks that could be used to promote effectiveness and add value to the construction projects. The proposed framework will also aid construction practitioners in managing construction supply chain risks in Pakistan construction industry